2011
DOI: 10.1038/bmt.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem-cell transplantation following solid-organ transplantation in children

Abstract: Reports of hematopoietic stem-cell transplantation (HSCT) following solid-organ transplantation have been described in adults mainly as case reports. These reports demonstrate feasibility but likely do not reflect true outcomes due to a positive reporting bias. We report herein the outcomes of all our pediatric recipients of allogeneic HSCT following previous solid-organ transplantation between 2000 and 2009. Four children were identified. Two patients underwent heart transplantation followed by cord-blood all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Allogeneic hematopoietic stem cell transplantation has been reported as a salvage therapy for PTLD in few case reports [69], but the available results were disappointing. …”
Section: Therapymentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation has been reported as a salvage therapy for PTLD in few case reports [69], but the available results were disappointing. …”
Section: Therapymentioning
confidence: 99%
“…Schechter et al . reviewed pediatric transplant data spanning 2000 to 2009 and found that there were limited data on patients receiving HSCT and solid organ transplant [ 13 ]. Many of these patients received a secondary transplant due to either severe aplastic anemia following liver transplantation or post-transplant lymphoproliferative disease following solid organ transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although there was the potential for a T-cell mediated immune response by the stem cell donor's lymphocytes against the previously transplanted heart, we saw no sign of this during the peri-transplant period. A literature search found several previous case reports of HCT in recipients of cardiac transplantation [1013]. All but one patient survived HCT without rejecting their cardiac graft.…”
Section: Discussionmentioning
confidence: 99%
“…All but one patient survived HCT without rejecting their cardiac graft. However, the peri-transplant mortality and morbidity was high, reflecting the fine balance between risks of serious infections and the need for ongoing immunosuppression [1013]. …”
Section: Discussionmentioning
confidence: 99%